Lands that hold one spellbound : a story of East Greenland - Apollonio, Spencer (Northern lights series, 2008)
Offers an history of East Greenland. This book summarises indigenous settlements over four millennia and describes European explorations since the Norse. It recounts each of the European and American expeditions, relying on the explorers' original accounts, as well as on the author's narration.